Trophic Transfer of Macroalgal Fatty Acids in Two Urchin Species: Digestion, Egestion, and Tissue Building - Schram, Julie B.; Kobelt, Julia N.; Dethier, Megan N.; Galloway, Aaron W. E. (Frontiers in Ecology and Evolution, 2018)
Sea urchins are ecosystem engineers of nearshore benthic communities because of their influence on the abundance and distribution of macroalgal species. Urchins are notoriously inefficient in assimilation of their macroalgal diets, so their fecal production can provide a nutritional subsidy to benthic consumers that cannot capture and handle large macroalgae. We studied the assimilation of macroalgal diets by urchins by analyzing the profiles of trophic biomarkers such as fatty acids (FAs). We tracked macroalgal diet assimilation in both Strongylocentrotus droebachiensis and S. purpuratus. Juvenile S. droebachiensis and adult S. purpuratus were maintained for 180 and 70 days, respectively, on one of three monoculture diets from three algal phyla: Nereocystis luetkeana, Pyropia sp., or Ulva sp. We then analyzed FA profiles of the macroalgal tissue fed to urchins as well as urchin gonad, gut, digesta, and egesta (feces) to directly evaluate trophic modification and compare nutritional quality of urchin food sources, urchin tissues, and fecal subsidies. In the S. purpuratus assay, there were significantly more total lipids in the digesta and egesta than in the algae consumed. The FA profiles of urchin tissues differed among urchin species, all diets, and tissue types. Despite these differences, we observed similar patterns in the relationships between the urchin and macroalgal tissues for both species. Egesta produced by urchins fed each of the three diets were depleted with respect to the concentration of important long chain polyunsaturated fatty acids (LCPUFAs), but did not differ significantly from the source alga consumed. Both urchin species were shown to synthesize and selectively retain both the precursor and resulting LCPUFAs involved in the synthesis of the LCPUFAs 20:4⍵6 and 20:5⍵3. S. droebachiensis and S. purpuratus exhibited consistent patterns in the respective depletion and retention of precursor FAs and resulting LCPUFAs of Pyropia and Ulva tissues, suggesting species level control of macroalgal digestion or differential tissue processing by gut microbiota. For both S. droebachiensis and S. purpuratus, macroalgal diet was a surprisingly strong driver of urchin tissue fatty acids; this indicates the potential of fatty acids for future quantitative trophic estimates of urchin assimilation of algal phyla in natural settings.